FLO Facilitation Guide : Facilitating Learning Online - Currie, Sylvia; Riessner, Sylvia; Bennett, Gina; Blom, Beth Cougler; BC Open Textbook Project; BCcampus (BCcampus, 2019)
"The FLO Facilitation Guide is a companion resource for the five facilitating learning online courses. It is designed to help individuals prepare and facilitate these courses as well as any courses that emphasize facilitating in a community of learners and supporting collaboration and reflective practice. The guide was written by experienced FLO facilitators and learning designers and includes exemplary contributions to the courses, instructions, ideas, materials, and facilitation tips and strategies. It is presented with a consistent structure for each course, making it easy to zone in on exactly what is relevant"--BCcampus website.
This work is licensed under the Creative Commons Attribution International CC-BY.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on online resource; title from pdf title page (viewed on June 1, 2020).
Keywords: Web-based instruction; Computer-assisted instruction; Distance education; Open learning; Electronic books